Status Markets and Standard Markets in the Global Garment Industry - Patrik Aspers (Max Planck Institute for the Study of Societies, 2005)
The purpose of this paper is to analyze the social construction of order in two adjacent markets in the production flow of the global garment industry. The consumer market is identified as a status market, while the production market is defined as a 'standard' market. In a status market, order is maintained because the identities of actors on both sides of the market are ranked according to status, which is a more entrenched social construction than the commodity traded in the market. In a market characterized by standard the situation is reversed: the commodity is a more entrenched social construction than the identity rankings of actors in the market. The study ties together production and consumption through an analysis of commodities in the market. The results are based on extensive fieldwork and interviews, as well as textual material from four countries: India, Sweden, Turkey and the UK. – – Ziel dieses Discussion Papers ist die Analyse der sozialen Konstruktion von Ordnung in zwei angrenzenden Märkten innerhalb der Produktionskette der globalen Bekleidungsindustrie. Der Endverbrauchermarkt wird als "Statusmarkt", der Produktionsmarkt als "Standardmarkt" definiert. In einem Statusmarkt wird die Ordnung dadurch aufrecht erhalten, dass die Akteuridentitäten auf beiden Seiten des Marktes eine Rangfolge gemäß dem Status der Akteure haben. Diese Statushierarchie ist eine fester gefügte soziale Konstruktion als die gehandelte Ware an sich. In einem durch Standard charakterisierten Markt ergibt sich eine umgekehrte Situation: die Handelsware stellt eine gefestigtere soziale Konstruktion als die Statushierarchie der Akteuridentitäten im Markt dar. Durch eine Analyse der Handelsware verbindet diese Studie Produktion und Konsum miteinander. Die Ergebnisse und das Textmaterial basieren auf umfassender Feldforschung und Interviews in vier Ländern: Indien, Schweden, Türkei und Großbritannien.
Keywords: 300